The Effectiveness of the Prosecution of Narcotics Crime at the Pati District Attorney - Putri, Riztyananda Siswoyo (Law Development Journal, 2022)
The application of imprisonment for abusers, especially narcotics addicts, is seen as an inappropriate action because imprisonment only gives grief to the perpetrator without curing his dependence on narcotics. This writing aims to analyze the effectiveness of the prosecution of narcotics crimes at the Pati District Attorney's Office in the conception of legal certainty, obstacles to the implementation of prosecutions for narcotics crimes at the Pati District Attorney's Office and their solutions. The approach used in this study is a sociological juridical approach, namely by finding legal realities experienced in the field or an approach that is based on problems regarding juridical matters and existing facts. The research specification used in this research is descriptive analysis. Using descriptive qualitative is one of the types of research that is included in the type of qualitative research. The analytical knife in this paper uses the theory of legal effectiveness and legal certainty. The results of the research show that the effectiveness of the implementation of the prosecution runs well and effectively as long as the Public Prosecutor carries out according to statutory regulations. The effectiveness of the prosecution of narcotics crimes at the Pati District Attorney can run well and effectively if it is carried out in accordance with applicable laws and regulations and pays attention to the implementation carried out by the Attorney General's Office, and the role of the community in helping uncover criminal acts.